An output-polynomial time algorithm to determine all supported efficient solutions for multi-objective integer network flow problems - Könen, David; Stiglmayr, Michael (Discrete Applied Mathematics, 2025)
This paper addresses the problem of enumerating all supported efficient solutions for a linear multi-objective integer minimum cost flow problem (MOIMCF). It derives an output-polynomial time algorithm to determine all supported efficient solutions for MOIMCF problems. This is the first approach to solve this general problem in output-polynomial time. Moreover, we prove that the existence of an output-polynomial time algorithm to determine all weakly supported nondominated vectors (or all weakly supported efficient solutions) for a MOIMCF problem with a fixed number of d≥3 objectives can be excluded unless P=NP.